(untitled) (The Research of Medical Science Review, 2025)
Background: Acute respiratory failure (ARF) is a critical condition requiring timely intervention. Non-invasive ventilation (NIV) has gained prominence as a treatment modality, reducing the need for invasive mechanical ventilation and improving clinical outcomes. Objective: To evaluate the effectiveness of non-invasive ventilation in improving oxygenation and ventilation in patients with acute respiratory failure (ARF). Methods: This analytical cross-sectional study was conducted at the ICU of Integrated Medical Care Hospital over four months. A total of 140 patients aged 20-90 years, diagnosed with either Type I or Type II respiratory failure, requiring NIV assistance, were included. Patients with severe neurological impairment, facial trauma, or progressive neuromuscular diseases were excluded. Arterial blood gas (ABG) analysis, respiratory rate, and NIV success rates were assessed. Data were analyzed using SPSS 22.0. Results: The study included 140 patients (52.14% males, 47.86% females) with a mean age of 64.78 ± 8.98 years. COPD was the most prevalent diagnosis (49.3%), followed by pneumonia (21.4%), ARDS (15.7%), and acute cardiogenic pulmonary edema (13.6%). NIV was successful in 77.14% of cases, with a 40% overall mortality rate. Intubation was required in 25% of cases. NIV resulted in statistically significant improvements in respiratory rate, PaO2, pH, and PCO 2 (p < 0.05). Conclusion: This study concluded that, NIV demonstrated significant efficacy in improving oxygenation, ventilation, and acid-base balance in ARF patients, reducing the need for invasive mechanical ventilation. The findings underscore its role as a preferred intervention in critically ill patients.